The Effect of Interpersonal Communication On Employee Performance At The Sidikalang District Office, Dairi Regency - Dameika Tambunan; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the effect of interpersonal communication on employee performance at the Sidikalang District Office, Dairi Regency. This study uses a quantitative approach with a casual associative research design. The study population includes all 48 employees of the Sidikalang District Office, with a saturated sampling technique. Data were collected through questionnaires and analyzed using simple linear regression with the help of SPSS software version 25.0. The results of the study indicate that interpersonal communication has a positive and significant effect on employee performance. The regression coefficient of 1.236 indicates that every 1 point increase in interpersonal communication will increase employee performance by 1.236 points. The results of the t-test show a t-count value of 8.508, greater than the t-table of 2.01290, with a significance value of 0.000 <0.05, which strengthens the significant effect. The determination coefficient analysis shows an Adjusted R Square value of 0.611, which means that interpersonal communication explains 61.10% of employee performance variability, while the remaining 38.90% is influenced by other factors not examined in this study. Interpersonal communication dimensions such as openness, empathy, positive feelings, and equality have been shown to play an important role in improving employee performance. This study recommends interpersonal communication training, periodic communication evaluation programs, and strengthening an inclusive work culture to improve employee performance.